Indonesian Politeness Islamic Kindergarten Teacher Al Ittifaqiah Indralaya - Nisartika, Nisartika; Fitriani, Yessi; Utami, Puspa Indah (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe language skills which are very important, one of which is the Al Ittifaqiah Indralaya Islamic Kindergarten teachers, because in communicating, all teachers are required to use polite language. In building character one of them is language, both forms of obedience and violations that exist in the utterances spoken by the teacher at the Al Ittifaqiah Indralaya Islamic Kindergarten. This study examines the pragmatic aspects of teacher language politeness in the Al Ittifaqiah Indralaya Islamic Kindergarten, the research examines speech when teachers converse during non-formal hours that take place at school and based on the types of maxims used. Language politeness was chosen because it will be used as an evaluation of the language used by the teacher. The results of this study indicate that the utterances in Al Ittifaqiah Islamic Kindergarten obtained 20 utterances consisting of 14 utterances containing politeness maxims and 6 utterances that deviate from politeness maxims. Of the 14 utterances of the Al Ittifaqiah Indralaya Islamic Kindergarten teacher's utterances which contain politeness maxims, namely: 3 utterances of wisdom maxim (21.42%), 2 utterances of generosity maxim (14.28%), 1 utterance of praise maxim (7, 14%), the maxim of humility is 1 utterance (7.14%), the maxim of response or apology is 3 utterances (21.42%), the maxim of agreement is 2 utterances (14.28%), the maxim of sympathy is 2 utterances (14.28%), Of the 6 utterances of the Al Ittifaqiah Indralaya Islamic Kindergarten teacher who deviated from the politeness maxim, namely: the maxim of humility was 4 utterances (66.67, the maxim of sympathy was 2 utterances (33.33%).